Pelatihan dan Pendampingan Usaha Kreatif VCO Desa Palingi Timur Konawe Kepulauan - Rita L Bubun; Amir Mahmud; Sumarlin Sumarlin (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
This activity was purposed to enhance the knowledge and skill of partner group (Ibu-ibu PKK) in business creative processing coconut to be virgin coconut oil (VCO). Training and mentoring were conducted in July 2019 at Palingi Timur Village, North of Wawonii Subdistrict, Konawe Kepulauan Regency Southeast of Sulawesi Province. Implementation methode was the establishment of cooperation with the goverment in Palingi Timur Village, socialization, training and mentoring partner group. The result showed that training and mentoring business creative of VCO were enhance until 95% of knowledge and skill of processing partner in Palingi Timur Village, and than they have had skill to utilizing and processing of local resources.